The 2005 U.S. defense budget: In line with defense transformation? - Benjamin Schreer (Stiftung Wissenschaft und Politik (SWP), 2004)
Apart from minor changes, Congress approved the Bush Administration's proposal for the 2005 defense budget at the end of July. Spending on national defense will increase for the seventh year running, amounting to 417.5 billion for the coming year in regular appropriations plus 25 billion for military operations in Iraq and Afghanistan. Is the money well spent for defense transformation? Are the lessons of the most recent conflicts reflected in budgetary planning? (SWP Comments / SWP)
Keywords: 320